2015
DOI: 10.1080/15384047.2015.1108496
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA MEG3 is downregulated in cervical cancer and affects cell proliferation and apoptosis by regulating miR-21

Abstract: Recent research has found that long noncoding RNAs (lncRNAs) were involved in various human cancers. However, the role of these lncRNAs in cervical cancer remains unexplored. Therefore, we aimed to investigate the biological function of maternally expressed gene 3 (MEG3), a cancer-related lncRNA, and its underlying mechanism in cervical cancer. In this study, MEG3 expression of 108 patients' cervical cancer tissues and adjacent normal tissues was detected by quantitative real-time PCR analysis (qRT-PCR), and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
226
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(236 citation statements)
references
References 27 publications
6
226
0
1
Order By: Relevance
“…Previous studies have suggested that MEG3 increased the p53 activity in cancer cells [24, 25]. Because pulmonary hypertension and cancers have similar pathological processes, like cell proliferation increased and apoptosis decreased.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested that MEG3 increased the p53 activity in cancer cells [24, 25]. Because pulmonary hypertension and cancers have similar pathological processes, like cell proliferation increased and apoptosis decreased.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, an increasing study have evidenced that lncRNAs can act as a competing endogenous RNA (ceRNA) via sponging miRNAs [13, 14]. In previous studies, MEG3 has been described to be a ceRNA that regulate miR-21 [15, 16], miR-1297 [17], and miR-140-5p [18]. Thus, we speculated that MEG3 may serve as a ceRNA which connecting some other miRNAs in pNETs.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Recent literatures reported that aberrant lncRNA expression is observed in almost all malignant human tumors and is involved in tumorigenesis by acting as oncogenes or tumor suppressor genes. [8][9][10] Tumor suppressor candidate 7 (TUSC7) is an antisense RNA gene consisted of four exons and located at 3q13.3. 11 TUSC7 has no protein-coding potential and belongs to lncRNAs.…”
Section: Introductionmentioning
confidence: 99%